The nature of galactic bulges from SAURON absorption line strength maps - Peletier, R; Falcón-Barroso, J; Ganda, K; Bacon, R; Cappellari, M; Davies, R; De Zeeuw, P; Emsellem, E; Krajnović, D; Kuntschner, H; McDermid, R; Sarzi, M; et al. (2006)
We discuss SAURON absorption line strength maps of a sample of 24 early-type spirals, mostly Sa. From the Lick indices H, Mgb and Fe 5015 we derive SSP-ages and metallicities. By comparing the scaling relations of Mg b and H and central velocity dispersion with the same relation for the edge-on sample of Falcn-Barroso et al. (2002) we derive a picture in which the central regions of Sa galaxies contain at least 2 components: one (or more) thin, disc-like component, often containing recent star formation, and another, elliptical-like component, consisting of old stars and rotating more slowly, dominating the light above the plane. If one defines a bulge to be the component responsible for the light in excess of the outer exponential disc, then many Sa-bulges are dominated by a thin, disc-like component containing recent star formation. © 2007 International Astronomical Union.